Characterizations of Human UDP-Glucuronosyltransferase Enzymes in the Conjugation of p-Cresol. (18th May 2020) - Rong, Yan; Kiang, Tony K L
Abstract: p -Cresol is a uremic toxin that is formed by intestinal microbiota and extensively conjugated by first-pass metabolism. p -Cresol glucuronide exerts various forms of cellular toxicity in vitro and is accumulated in the plasma of subjects with kidney disease, where associations with adverse cardiovascular and renal outcomes are evident. The objective of this study was to determine the contributions of human UDP-glucuronosyltransferase (UGT) enzymes in the formation of p -cresol glucuronide. Utilizing commonly expressed hepatic or renal human recombinant UGTs (ie, hrUGT1A1, 1A3, 1A4, 1A6, 1A7, 1A8, 1A9, 1A10, 2B4, 2B7, 2B10, 2B15, and 2B17), hrUGT1A6 and hrUGT1A9 exhibited the highest catalytic activities in the generation of p -cresol glucuronide. The kinetics of p -cresol glucuronide formation in hrUGT1A6 and pooled human liver microsomes were best described by the Hill equation and in hrUGT1A9 and pooled human kidney microsomes by substrate inhibition. Using inhibitory and selective UGT inhibitors (ie, acetaminophen or amentoflavone for UGT1A6 and niflumic acid for UGT1A9), UGT1A6 was identified the predominant enzyme responsible for p -cresol glucuronide production in pooled human liver (78.4%–81.3% contribution) and kidney (54.3%–62.9%) microsomes, whereas UGT1A9 provided minor contributions (2.8% and 35.5%, respectively). The relative contributions of UGT1A6 (72.6 ± 11.3%, mean ± SD) and UGT1A9 (5.7 ± 4.1%) in individual human liver microsomes from 12 adult donors were highly variable, where an inverse association ( R = −.784, p = .003) between UGT1A6 contribution and UGT1A9 probe substrate activity (ie, mycophenolic acid) was evident. Our novel findings provide valuable tools for conducting further mechanistic studies and for designing clinical interventions to mitigate the toxicities associated with p -cresol glucuronide.